Frequent source plasma donors are not at risk of iron depletion: the Ferritin Levels in Plasma Donor (FLIPD) study. Issue 4 (9th March 2018) - Schreiber, George B.; Brinser, Roger; Rosa‐Bray, Marilyn; Yu, Zi‐Fan; Simon, Toby
Abstract : BACKGROUND: Whole blood and red blood cell (RBC) donors are at risk of iron deficiency. Since Source plasma (SP) donors have RBCs returned during apheresis, risk of iron depletion appears low. However, SP donors can donate frequently and assessment of frequent donor iron status is needed. STUDY DESIGN AND METHODS: A total of 1254 SP donors were enrolled in four frequency groups determined by donations in the prior 12 months: no donations and 1 to 24, 25 to 69, and 70 or more donations. Ferritin was determined for each donor. Donors with ferritin levels of less than 12 ng/mL were classified as having absent iron stores (AIS). RESULTS: Compared to new donors, ferritin for females was higher in each successive frequency group. For 70 or more donations, ferritin was 13 ng/mL higher than in new donors (p = 0.02). For males, 1 to 24 donations had the highest ferritin levels. Compared to new donors, highest‐frequency donors had lower ferritin levels, 114 ng/mL versus 100 ng/mL (p = 0.14). Age for females and males increased with each successive frequency group. Age adjustment resulted in smaller ferritin differences for females and larger differences for males in the high‐frequency groups; AIS for females was highest in new donors (7%) and lowest in the highest‐frequency group (1%). In aggregate, AIS occurred in less than 1% of all male donors. Male new and highest‐frequency donors had 1% AIS with none in the other groups. CONCLUSION: Few SP donors have iron depletion and it is not higher in frequent donors. Frequent SP donation does not adversely impact iron stores. Thus, monitoring donor iron status or iron supplementation is not necessary.